PENERAPAN APLIKASI SIPEDIS (SISTEM PENEGAKAN DISIPLIN) PADA KPPBC TMP B MAKASSAR - Iwan Saktiawan (Jurnal Administrasi Negara, 2020)
The Directorate General of Customs and Excise, in this case the Office of Makassar Customs and Excise Supervision and Service Office has set up a mechanism for enforcing discipline on officials and employees in all work units which has started to be implemented. In that way, discipline in uniform and sports clothing (for Friday morning gymnastics exercise), discipline in attendance and working hours, and discipline in attitude and behavior could be maintained. The problem that occurs inits implementation is that the process of recording employee violations by the Disciplinary Enforcement Team is still in manual mode, not paperless, and requires transparency that can be accessed in real time over the discipline control of all employees. The purpose of this study is to create an application system for recording violations in an electronic discipline enforcement process that makes it easy for the Disciplinary Enforcement Team to conduct violation administration. This research is a form of applied research conducted with a qualitative approach. Data were collected through observation, interviews, document reviews, and documentation in order to obtain information regarding the development of employees. Three informants were involved in this study. This research resulted in an application as a solution to facilitate the implementation of disciplinary processes that are based on applications, accessible via mobile devices, thus, expected to improve employee discipline, as well as a means of monitoring by leaders about the scale of discipline violations. Therefore, for effective enforcement of employee discipline within the organization, it is necessary to use SIPEDIS (Discipline Enforcement System) as a means that is able to provide convenience in its implementation.